Study protocol: childhood outcomes of fetal genomic variants: the PrenatAL Microarray (PALM) cohort study - Lisa Hui; Cecilia Pynaker; Joanne Kennedy; Sharon Lewis; David J. Amor; Susan P. Walker; Jane Halliday; On behalf of the PALM cohort study group (BMC, 2021)
Abstract Background The implementation of genomic testing in pregnancy means that couples have access to more information about their child's genetic make-up before birth than ever before. One of the resulting challenges is the management of genetic variations with unclear clinical significance. This population-based study will help to close this critical knowledge gap through a multidisciplinary cohort study of children with and without genomic copy number variants (CNVs) diagnosed before birth. By comparing children with prenatally-ascertained CNVs to children without a CNV, we aim to (1) examine their developmental, social-emotional and health status; (2) measure the impact of prenatal diagnosis of a CNV on maternal perceptions of child health, behavior and development; and (3) determine the proportion of prenatally-ascertained CNVs of unknown or uncertain significance that are reclassified as benign or pathogenic after 2 or more years. Methods This study will establish and follow up a cohort of mother-child pairs who have had a prenatal diagnosis with a chromosomal microarray from 2013-2019 in the Australian state of Victoria. Children aged 12 months to 7 years will be assessed using validated, age-appropriate measures. The primary outcome measures will be the Wechsler Preschool and Primary Scale of Intelligence IV (WPSSI-IV) IQ score (2.5 to 7 year old's), the Ages and Stages Questionnaire (12-30 months old), and the Brief Infant- Toddler Social and Emotional Assessment (BITSEA) score. Clinical assessment by a pediatrician will also be performed. Secondary outcomes will be scores obtained from the: Vineland Adaptive Behavior Scale, Maternal Postnatal Attachment Questionnaire, the Vulnerable Child Scale, Profile of Mood States, Parent Sense of Competence Scale. A descriptive analysis of the reclassification rates of CNVs after ≥2 years will be performed. Discussion This study protocol describes the first Australian cohort study following children after prenatal diagnostic testing with chromosomal microarray. It will provide long-term outcomes of fetal genomic variants to guide evidence-based pre-and postnatal care. This, in turn, will inform future efforts to mitigate the negative consequences of conveying genomic uncertainty during pregnancy. Trial registration ACTRN12620000446965p ; Registered on April 6, 2020.